A STUDY OF REFUSAL STRATEGY USED BY ENGLISH TEACHERS IN MADIUN REGENCY IN DECLINING AN INVITATION, AN OFFER AND A SUGGESTION - Hastuti, Maya (Universitas Muhammadiyah Surakarta, 2014)
The aim of this study is to investigate strategies and politeness in rejection of the invitation, offer, and suggestions by English teacher in Madison County. This study uses the theoretical framework of Takahashi , Beebe and Uliss - Weltz. Data was collected using Mechanical Completion of Discourse (Discourse Completion Technique). The data source is the 38 English teachers, 14 men and 24 women who teach in junior high schools in Madison County. The results showed as follows: (1) The English teacher at junior high school in Madison County implemented two semantic formula of direct and indirect strategies in three acts of rejection (invitations, offers and suggestions). (2) Indirect strategy in the rejection of the dominant is the supply and advice directly while the dominant strategy used in the rejection of the invitation.